PEMANFAATAN SISTEM AGROFORESTRY TERHADAP PENDAPATAN PETANI DI KELOMPOK TANI HUTAN NEKAMESE, DESA EKATETA, KECAMATAN FATULEU, KABUPATEN KUPANG, PROVINSI NUSA TERNGGARA TIMUR - Runi Febriani Boimau; Maria M. E. Purnama; Mamie E Pelondo'u (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
‘Nekamese’ forest farmer group is one of the forest farmer groups located in Diklat Sesimeni Sanam forest area, Kupang Regency. This study aims to determine the benefits of applying the agroforestry system to the income of farmers in ‘Nekamese’ forest farmer group in Ekateta Village, Fatuleu District, Kupang Regency, East Nusa Tenggara Province. This data collection technique consists of interview and observation. Based on the research results, ‘Nekamese’ forest farmer group applies an Agroforestry system with an Agrosilvopastura pattern where the Agroforestry land managed is planted with agricultural plants such asZea mays L., Capsicum annum L., Musa sp,Brasissca chinensis Var,Cocos mucifera and Allium cepa L.;also forestry plants such as Gmelina arborea Roxb,Swietenia mahagoni, Cassia siamea, Paraseriantis falcataria, Santalum album L.,Vachellia leucophala and there are also livestock raising such as cows, goats and pigs. The contribution of Agroforestry and non-agroforestry to the farmers’ income in‘Nekamese’ forest farmer group are for Agroforestry income is IDR 135.185.000 with the percentage is 81.35% per year and non-agroforestry is IDR 31,000,000with thepercentage is 18.65% per year. This shows that the Agroforestry system has a very important role for the needs and income of farmers in ‘Nekamese’ forest farmer groups.